Waging a good war : a military history of the Civil Rights Movement, 1954-1968 - Ricks, Thomas E. (Farrar, Straus and Giroux, 2022)
"A new history of the Civil Rights Movement with an emphasis on its nonviolent use of military tactics and strategy"--